Mechanical properties and metallurgical features of new and ex vivo used Reciproc Blue and Reciproc. (27th September 2019) - Generali, L.; Puddu, P.; Borghi, A.; Brancolini, S.; Lusvarghi, L.; Bolelli, G.; Consolo, U.; Pedullà, E.
Abstract: Aim: To compare the mechanical properties and metallurgic features of new and used Reciproc Blue and Reciproc instruments. Methodology: A total of 120 R25 Reciproc Blue and R25 Reciproc instruments were used. The morphological, chemical, mechanical, thermal and phase composition characteristics of new and ex vivo used files were investigated by scanning electron microscopy (FEG‐SEM) with energy dispersive X‐ray spectroscopy (EDS), focused ion beam analysis (FIB), micro‐Raman spectroscopy, FEG‐SEM metallography, X‐ray diffraction (XRD), differential scanning calorimetry (DSC) and indentation tests. Usage‐induce degradation was evaluated. Ten new and ten used instruments per type were run until fracture occurred in a stainless steel artificial canal (60° angle of curvature, 4‐mm radius). Time to fracture and the length of the fractured fragment were recorded. Torque and angle of rotation at failure of ten new and ten used instruments for each type were measured according to ISO 3630‐1. The fracture surface of each fragment was examined. Two‐way analyses of variance was used to analyse the data statistically (α‐level 0.05). Results: SEM analysis revealed microcracks near the tip on both files after ex vivo usage tests. FIB imaging and micro‐Raman spectroscopy confirmed the presence of an oxide layer on the Reciproc Blue surface. There was no thinning of the coating after use. XRD revealed a reduction of martensite and R‐phase in Reciproc Blue after use. DSC analysis revealed different transformation temperatures for the instruments analysed. Reciproc Blue was significantly more flexible than Reciproc for both new and used samples ( P  < 0.05), and they were significantly more resistant to cyclic fatigue than Reciproc ( P  < 0.05). Ex vivo usage reduced the fatigue resistance of both files. Torsional resistance of Reciproc and Reciproc Blue was not reduced by simulated use ( P  > 0.05). Conclusions: The thermal treatment of Reciproc Blue was associated with a finer structure with smaller grains than Reciproc, which increased its fracture resistance and was also responsible for its reduced hardness and lower elastic modulus. Both files were safe during ex vivo usage in severely curved canals.